Przyszłość bankowości elektronicznej w Polsce - Natalli, Krzysztof; Szczepanik, Maciej (The Future of E-banking in Poland, 2006)
Although e-banking has been used in Poland for distribution of banking products for about 15 years, it is still the fastest developing distribution channel (especially i-banking). In recent years we have been able to observe quick increase of number of clients interested in using this kind of services and number of banks deciding to offer it to their clients. Within the present publication, its authors make a review of e-banking tools and then present the SWOT analysis of e-banking in Poland. The article compares strengths of e-banking with its weak-nesses and opportunities with threats. As the assumption the authors make conclusions about the future of e-banking in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 201-215